2002
DOI: 10.1023/a:1022986331231
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Activated neutrophils which produce certain proteases, such as elastase and reactive oxygen species (ROS) are involved in oxidative stress and inflammation. In the present study, we have shown that nicardipine, a calcium channel blocker, affects the release of elastase and superoxide anion radicals (O(2-)) in vitro during human and rabbit neutrophil respiratory bursts. The drug inhibited the release of elastase and O(2-) by fMLP (N-formyl-methionylleucin-phenylalaninin), calcium ionophore (A23187) and PMA (pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Calcium channel blockers have also been investigated for their potential antioxidative properties in a minor extent as compared to the above described antihypertensive drugs [127][128][129]. Amlodipine decreases oxidative stress by reducing malondialdehyde and increasing erythrocyte sodium-potassium adenosine triphosphatase and SOD levels in essential hypertensive patients [127].…”
Section: Anti-hypertensivesmentioning
confidence: 99%
“…Calcium channel blockers have also been investigated for their potential antioxidative properties in a minor extent as compared to the above described antihypertensive drugs [127][128][129]. Amlodipine decreases oxidative stress by reducing malondialdehyde and increasing erythrocyte sodium-potassium adenosine triphosphatase and SOD levels in essential hypertensive patients [127].…”
Section: Anti-hypertensivesmentioning
confidence: 99%
“…The possibility that 1,4-DHP-based calcium antagonists exert an antiatherosclerotic action ( via inhibition of LDL oxidation and other mechanisms) has been proved by many experimental data [ 165 ] and several clinical trials. Besides antihypertensive effect, nicardipine was shown to possess antioxidative and antielastase activity [ 165 , 166 ]. These properties may be useful for prevention of inflammatory reaction which is relevant for hypertension pathogenesis.…”
Section: 14-dihydropyridines: a Separate Group Of Bioantioxidantsmentioning
confidence: 99%
“…In neutrophils, pharmacological inhibitors of L-type channels have been reported to reduce the Ca 2+ response of human polymorphonuclear neutrophils (PMNs) to a neuropeptide ( 63 ), and to reduce the release of elastases and the production of ROS from these cells via diminished cytosolic Ca 2+ mobilization and PKC activation ( 64 ). In monocytes, it was similarly reported that nifedipine dampens superoxide production and that in addition it directly contributes to reducing PKC activity ( 65 ).…”
Section: L-type Channels In Immune Cells Of the Myeloid Lineagementioning
confidence: 99%